The Effectiveness of Trypsin Modulating Oostatic Factor (TMOF) and Combination of TMOF with Bacillus thuringiensis Against Aedes aegypti Larvae in the Laboratory - YS Lau; S Sulaiman; H Othman (Tehran University of Medical Sciences, 2011)
Background: Trypsin Modulating Oostatic Factor (TMOF) terminates trypsin biosynthesis in adult and larval mosquito gut. It will inhibit the growth and development of mosquito larvae feeding on it resulting in death by starvation. The objective of this study is to determine the effective dose of Pichia-TMOF and the combination of Pichia-TMOF with Bacillus thuringiensis (Bt) as larvicide on Ae. aegypti larvae. Methods: Aedes aegyptifirst-instar larvae were exposed to various doses of Pichia-TMOF, Bt and combination of Pichia-TMOF and Bt.  The development of the larvae were observed and recorded daily during the bioassay larval test until the adult emergence. Results: The results showed that 400 ppm Pichia-TMOF and 300 ppm Pichia-TMOF were able to cause 100% and 67% cumulative mortality on Ae. aegypti larvae on 8th day respectively. At 200 ppm, 100 ppm and 50 ppm concentration Pichia-TMOF showed obvious stuntedeffect on Ae. aegypti larvae. Moreover, the combination of 400 ppm Pichia-TMOF with 0.1 ppm Bt showed synergistic effect on Ae. aegypti. Conclusion: Pichia-TMOF inhibited trypsin biosynthesis is potential to act in larval gut causing stunted growth and larval development and causing mortality.The combination of Pichia-TMOF and Bt increased the effectiveness in causing larval mortality.